Desenvolvimento de instrumentação científica em nanotecnologia: inferências para nanoespectroscopia Raman a partir de Technology Roadmapping retrospectivo adaptado de duas tecnologias consolidadas - Márcia Dias Diniz Costa (2021)
Scientific instrumentation refers to devices used by scientists for the investigation of nature. The ability to develop and produce instruments gives a country sovereignty, as it allows it to create its own scientific agenda, with significant implications for technological development, making it possible to add value to products and / or processes. In the case of Brazil, the high external dependence on scientific instrumentation makes science more vulnerable to factors such as exchange rates and policies to encourage ST&I, which is particularly critical in the case of nanotechnologies, identified as belonging to one of the areas responsible for the next cycle of economic growth. The objective of this thesis is to identify influencing factors in the trajectory of creation, diffusion and commercialization of scientific nanotechnology instruments and to generate learning for the development of the nanoespectrometer based on TERS (tip-enhanced Raman spectroscopy), a scientific instrument of nanotechnology that is still predominantly in the context of fundamental research, with relevant participation from Brazil. The question that we want to answer with this work is: what are the factors (mainly technical and institutional) that mediate or influence the trajectory of a cutting-edge scientific instrumentation technology in nanotechnology? To this end, an adapted, retrospective, historical technology roadmapping (TRM) approach was proposed and implemented for two already consolidated scientific instruments of nanotechnology – the electron microscope (EM) and the scanning probe microscope (SPM), also applied to the recent trajectory of TERS. The evolution of publications in the Scopus database was proposed as an indicator of demand for the instruments and to locate the emergency phases. Retrospective roadmaps for the three techniques were proposed, and their main elements (layers, phases and transitions) were located. The qualitative analysis of historical events proved to be useful to elucidate the influencing factors in the development trajectories, especially in the initial phases of the instrumentation emergency, when the number of publications is still relatively low. The results suggest that the most significant influencing technical factors are: (a) perfectioning of the instrument, by varying components to improve the results of experimental measurements; (b) use of the instrument in new applications and, at the same intensity, development of products that make such applications feasible. As for institutional factors, the analysis identified the participation of the actors of the triple helix, with emphasis on the academy, which develops scientific instrumentation motivated, mainly, to answer their research questions. The analyzes suggest that electron microscopy is still growing, and the SPM has reached its maturity. TERS seems to be starting the growth phase, with the expansion of its applications, but there is a gap in the availability of commercial instruments to make these applications viable in the market and to feed the dynamics between the emergency phases that will lead to the diffusion of the technique and expanding the user community. The main motivation of this thesis is to shed light on the likely future trajectory of TERS and, with this, to assist the recent entrepreneurial initiatives of a Brazilian laboratory with scientific excellence and worldwide recognition in this technique.